Optical Assessment of Titanium Oxide Employed in Phosphor-Transmuted WLED Devices - Le, Phan Xuan; Loan, Nguyen Thi Phuong; Anh, Nguyen Doan Quoc (Science and Technology Indonesia, 2026)
Utilizing inexpensive PbO-B2O3-SiO2-ZnO glass as the host, a new environmentally friendly method for phosphor-transformed WLED utilizing Ce:YAG-doped glass and Titanium oxide (TiO2) was effectively created for this study. This method demonstrated good sintering behavior and elevated visible transparency with a sintering heat level reaching 750oC while avoiding influence on phosphor samples. The optic characterization of WLED can be simply adjusted by only modifying the temperature, incorporating dosage, as well as sample breadth to suit the mucous sintering for phosphor within glass (PwG). The perfect sample amount is regulated, reaching 5 wt.% of the end combination, and the most suited thickness of samples is discovered to be 0.8 mm. As a consequence, the optimum heating condition is sintered at 700oC within 40 minutes. The built-in PwG WLED displays an elevated illuminating effectiveness of 134.33 lm/W, associated hue temperature of 4696 K, and hue rendering index of 68.5. PwG’s improved heat quenching ability when combined with traditional silicone resin and TiO2 makes it clear that the glass ceramic substance used today is highly practical for use in WLED apparatuses.